TEST OF SUKUN LEAVE (Artocarpus altilis) SOLUTION ON THE GROWTH OF BACTERIA Aeromonas hydrophila - Yulyawati Yulyawati; Iesje Lukistyowati; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT One of the plant (Artocarpusaltilis)is a plant that can be used as a drug and has many benefits, one of which is antibacterial to the disease Motile Aeromonad Septicemia (MAS). This research was conducted from February to August 2018 at the Laboratory for Fighting Pests and Diseases of Fish, Department of Aquaculture, Faculty of Fisheries and Marine, University of Riau. The purpose of the study was to determine the inhibitory potency of the breadfruit leaf solution in inhibiting the growth of Aeromonas hydrophila bacteria, the MIC (Minimum Inhibitory Concentration) dose and the toxicity of the solution of breadfruit leaves to immersion. The research method used is the experimental method using the KIRBY-BAUER disc method to reduce the level of error then repeated 3 times. Determination of treatment was PO control (Oxytetracyclin), P1 (100%), P2 (90%), P3 (80%), P4 (70%), P5 (60%), P6 (50%), P7 (40%) , P8 (30%), P9 (20%), P10 (10%), P11 (9%). The doses used in this study were 9% (900 ppm), 10% (1000 ppm), 20% (2000 ppm), 30% (3000 ppm) and controls . The results of this study indicate that the breadfruit leaf solution (Artocarpusaltilis) is able to inhibit the growth of A. hydrohila by presenting a 100% inhibition dose with an average of 10.56 mm and a minimum inhibition of 9%, giving an average inhibition of 6.46 mm. It can be said that the dose of MIC (minimum inhibitory concentration) of breadfruit leaf solution, at a dose of 10% with an average number of bacterial colonies of 268 Sel / mL, is the minimum dose capable of inhibiting the growth of A. hydrophila bacteria. The results of the LD50 toxicity tests of the breadfruit leaf solution on Siam ham (P.hypophthalmus) were immersed for 24 hours at a concentration of 1177 ppm. Keywords: Artocarpus altilis, Aeromonas hydrophila, antimicrobial, LD50